Dari Toleransi ke Kewaspadaan: Deteksi Dini Konflik Keagamaan oleh Tokoh Agama di Kota Kediri - Umam, Khairul; Anam, Masrul (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
Religious-based conflicts often generate widespread destructive impacts, making early prevention a strategic agenda not only for the state but also for all elements of society. This article seeks to analyze the potential sources of religious conflict in Kediri City—widely recognized as a space of tolerance—while examining the role of religious leaders in preventing these potentials from escalating into open conflict. The study employs content analysis of digital media combined with descriptive analysis to explore the social actions of religious leaders in managing conflict risks. The findings reveal four major sources of vulnerability: religious plurality that may trigger social segregation, issues surrounding the construction and activities of houses of worship, tensions in the celebration of religious holidays, and the penetration of extremist religious doctrines. In response to these vulnerabilities, religious leaders have initiated preventive measures such as monitoring socio-political conditions, facilitating regular interfaith dialogue, mediating conflicts peacefully, and fostering close collaboration with state institutions through interfaith forums. These findings underscore that early detection strategies grounded in religious leadership not only strengthen social cohesion but also provide a preventive model that can be replicated in other regions. Theoretically, this study contributes to conflict studies by demonstrating the interplay between structural, cultural, and religious factors in building an effective early warning system.